Highly antiproliferative neutral Ru(ii)-arene phosphine complexes. (30th January 2018) - Chotard, Florian; Dondaine, Lucile; Balan, Cédric; Bettaïeb, Ali; Paul, Catherine; Le Gendre, Pierre; Bodio, Ewen
Abstract : The introduction of a benzoate ligand dramatically increases the ruthenium uptake in cells, leading to a low micromolar IC50 . Abstract : Six ruthenium(ii )- and four gold(i )-phosphine based complexes were synthesized and fully characterized. Some of them displayed strong antiproliferative properties for several types of cancer including colon, breast, and lung. Notably, two of the Ru(ii ) complexes displayed an IC50 of around 2 μM, which is exceptional for these types of complexes. The dramatic impact of the nature of the arene coordinated on the ruthenium center was clearly evidenced.